AB1349 Safety and effectiveness of cosmetic minimaly invasive procedures among patients with systemic autoimmune disease. (12th June 2018) - Reitblat, O.; Lerman, T.T.; Reitblat, T.
Abstract : Background: Noninvasive or minimally invasive cosmetic dermatologic procedures are considered safe with low parentage of reported adverse events. However, reliable prevalence data regarding adverse event of such cosmetic procedures among patients with systemic autoimmune diseases are insufficient. Objectives: To assess the occurrence of adverse events and disease exacerbation associated with noninvasive or minimally invasive cosmetic dermatologic procedures, including those involving hyaluronic acid fillers, botulinum toxins and laser application among patients with systemic autoimmune diseases. Methods: Consecutive cases of patients suffering from autoimmune diseases and attending the rheumatology clinic for regular follow-ups, were asked about receiving cosmetic procedures during the last two years. Medical history, including clinical and laboratory signs of disease exacerbation after the date of the procedure, was retrospectively obtained from medical files of the patients included in the study. Patients were also asked about subjective disease exacerbation and local adverse events after the procedure. Results: During the three months of study period, 148 patients were inquired. Nineteen patients (89% females) underwent 23 cosmetic procedures in total. Thirty-nine percent had Rheumatoid arthritis (RA), 39% had Ankylosing spondylitis (AS) and 22% had other systemic connective tissue disease. Sixty seven percent were treated by Disease-modifying antirheumatic drugs (DMARDs), 28% by Biologic treatment and 5% did not receive any specific treatment. All patients were in remission during the cosmetic procedures. Forty three and a half percent of patients underwent hyaluronic acid injection, 21.7% botulinum toxin injection, 21.7% laser application, 8.7% mesotherapy and 4.3% silicon injection. None of the patients suffered from subjective disease exacerbation after the procedure. No changes in antibody titer and level of acute phase reactants (C-reactive protein and erythrocyte sedimentation rate) were noticed. Two patients (10.5%) experienced local oedema after filler injections. Both patients received Hydroxychloroquine treatment (one patient with RA and one with AS). Conclusions: Our results suggest that noninvasive or minimally invasive cosmetic dermatologic procedures, including energy, neurotoxin, and filler procedures, may be safe among rheumatological patients, and do not cause autoimmune systemic disease exacerbation when performed in periods of remission. Hydroxychloroquine may predispose to a higher occurrence rate of local site injection adverse events. Further studied are desired to investigate this phenomena. Disclosure of Interest: None declared